2019
DOI: 10.3168/jds.2018-15192
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of urease in yogurt fermentation with various combinations of Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus

Abstract: The protocooperation between Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus relies on metabolite exchanges that accelerate acidification during yogurt fermentation. Conflicting results have been obtained in terms of the effect of the Strep. thermophilus urease and the NH 3 and CO 2 that it generates on the rate of acidification in yogurt fermentation. It is difficult to perform a systematic study of the effects of urease on protocooperation because it is necessary to distinguish among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…However, there are conflicting views regarding the role of urease in yogurt fermentation. Yamauchi et al (2019) observed that urease deficiency severely reduced acidification rates and bacterial counts in fermented milk and con-…”
Section: Short Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are conflicting views regarding the role of urease in yogurt fermentation. Yamauchi et al (2019) observed that urease deficiency severely reduced acidification rates and bacterial counts in fermented milk and con-…”
Section: Short Communicationmentioning
confidence: 99%
“…The critical factor in the selection of S. thermophilus for application in fermented milk is its ability to rapidly metabolize lactose and produce acids. Its other essential aspects include its urease activity, proteolytic activity, and exopolysaccharide production (Iyer et al, 2010;Wu et al, 2014;Yamauchi et al, 2019).…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutant D-alanyl-lipoteichoic acid biosynthesis protein knockout L. plantarum CRL1506 strain (L. plantarum dltD) was obtained according to the method described by Yamauchi et al (12). Briefly, the dltD gene was obtained by PCR using primers No.…”
Section: Microorganismsmentioning
confidence: 99%
“…The stability of the mutated phenotype was confirmed, providing promising results regarding the potential use of ureasedeficient strains as starters in dairy fermentations (Ninova-Nikolova and Urshev, 2013). However, in a recent study employing urease deficient mutants it was suggested that urease activity is important for yogurt acidification and that its absence inhibits fermentation acceleration during protocooperation with L. bulgaricus (Yamauchi et al, 2019).…”
Section: Urea Metabolismmentioning
confidence: 99%